Pengembangan Kurikulum melalui Program Keterampilan Vokasional di Madrasah Aliyah Negeri (MAN) 1 Nganjuk - Mufida, Aninda Husna (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2023)
Education is the main key in the development and progress of a country. The bigger a country, the higher the quality of education it has. For this reason, it is necessary to develop and improve the education system in Indonesia as a form of awareness of the development of the quality of education. Schools as a place for students to understand, study and practice this science have at least a qualified curriculum as a benchmark in their learning. Not only by learning in the classroom, schools at least provide applied teaching as a way for schools to provide provisions and realize a knowledge while increasing the potential and talents of students. Knowledge and application of vocational skills is one of the keys in learning applied science and printing output that is ready to work.